The competitiveness of short sea shipping taking into account environmental, infrastructure and oil costs. A case study of the Tallinn-Warsaw Route. (1st January 2012) - Hilmola, Olli-Pekka
The economic growth of the former East European countries has been remarkable in recent decades. This has been mainly fuelled by transport, with a significantly growing use of road. This is true mostly for Poland and the three selected Baltic States (Latvia, Lithuania and Estonia) for the purposes of this paper. A weak competition against road found to have been created from 'short sea shipping' in the main leg and in the hinterland destinations. However, we saw that near future holds major changes in horizon like: planned new environmental and infrastructure payments/tolls as well as a seriously increasing price of oil (something we see to continue in future). In this paper, we present these forthcoming changes found in existing literature and knowledge, and portray changes in terms of cost implications in particular on the general cargo transported between Tallinn (Estonia) and Warsaw (Poland). Our results show that both analysed transport options – road and short sea shipping are going to face serious cost increases, and most probably the road transport will be weaker in its competitiveness in future . Mostly, the changes are explained by assuming an increasing price of oil.